IMPLEMENTATION OF BEHAVIORISM LEARNING THEORIES IN ARABIC LEARNING PLANNING - Syafe'i, Isop; Ulfah, Ai Fitria (STIQ Amuntai, 2020)
The purpose of this research to know the theory of learning behaviorism through BF Skinner's thinking in planning Arabic learning. This research method is literature study with qualitative approach, data is extracted through literature study and analyzed through content analysis. The primary data source in this study is The Theories of Learning by Ratna Willis Dahar. While secondary data in this study were obtained from literature exploration related to the discussion. The results of the analysis show that the BF Skinner theory can be applied in Arabic learning planning that is the material being studied is analyzed up to the units organically, the subject matter is used a module system, learning evaluation must be notified to students, if incorrectly corrected and if properly strengthened, more tests emphasized for the sake of diagnostics, in education prioritizing changing the environment to avoid violations so as not to punish, prioritizing the needs that will lead to operant behavior, the behavior desired by educators are rewarded, the desired behavior is analyzed in small ways, increasingly reaching goals, implementing mastery learning is to learn the material thoroughly according to each time because each child has a different rhythm.